Livelihood Diversification and Household Vulnerability to Climate Shocks in Rural Kenya - Philip K. Musyoka; Joseph Onjala (International Journal of Economics Development Research (IJEDR), 2023)
This study tests the hypothesis that livelihood diversification mitigates vulnerability to climate shocks among rural households in Kenya. The study is based on two waves of nationally-representative household survey data collected in 2005/06 and 2015/16. A measure of livelihood diversification in the sampled households was computed using Simpson Diversity Index. Comparison of means and correlation analysis was used to test the study’s hypothesis on a sample of 8,483 and 12,217 rural households in 2005/06 and 2015/16 respectively. Consistent with the study’s hypothesis, results indicate lower mean values of livelihood diversification indices for rural households that reported loss in welfare due to climate shocks compared to those that reported no adverse effects in both 2005/06 and 2015/16. Correlation analysis results indicate an inverse relationship between livelihood diversification and vulnerability to climate shocks for all sampled households. Distinctive and nuanced differences in results were found when analysis was disaggregated along income classes and agro-ecological zones. Sensitivity analysis confirmed robustness of the results. Based on these results, it is recommended that rural households be supported to pursue a diverse portfolio of income generating activities and assets in order to build resilience against climate shocks.